Policy and the social burden of bald eagle recovery. Issue 9 (5th July 2022) - Watts, Bryan D.; Byrd, Mitchell A.
Abstract: One of the challenges of applying endangered species policy on private property is striking an equitable balance between species protection and civil liberties. The future of many imperiled species depends on a public‐private trust. We estimate the social burden of managing bald eagles on private lands within the lower Chesapeake Bay (1976–2016). We quantify the area of private and government‐owned land deemed critical around nests and estimate the value of private properties as an index of burden. The bald eagle population increased from 30 to 1052 breeding pairs and the land within nest buffers increased from 384 to 10, 670 ha with >80% on private lands. Estimated value of private property "under guidelines" increased more than 900 fold. More than 94% of this burden was imposed after eagles reached recovery goals. Restricting activities on private lands to achieve diminishingly small conservation benefits threatens to undermine landowner participation in conservation efforts.